Kesiapsiagaan Bencana Perawat di Rumah Sakit Rujukan pada Area Rentan Bencana di Indonesia: Studi Deskriptif - Tuti Herawati; Arcellia Farosyah Putri (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2023)
Background. Indonesia based on its geographical, geological, hydrological and demographic conditions is prone to disasters. Pre-disaster preparedness in health services are very important phases in reducing the impact of a disaster. Nurses are health workers with the largest number in a hospital, and have an important role in a disaster.The purpose of this study was to explore nurses’ perception regarding disaster preparedness in referral hospitals in disaster-prone areas in Indonesia. Methods. This study was a cross-sectional study. The cluster random sampling technique was used in the recruitment of 217 respondents from 4 referral hospitals in Indonesia. Self-report questioner were utilized and it was modified from Disaster Preparedness Evaluation Tool (DPET) and Emergency Prepardeness information Questionairre (EPIQ). Univariate and bivariate analyses were applied to describe the data. Results. The mean age of the respondents was 37.6 ± 8.9 years and the average length of service was 14 years ± 9.6 years. Respondents were mostly female, had vocational education level, were married, worked in wards, worked as clinical nurse, had no disaster experience but worked in hospitals that had experienced disasters. The average of nurses’ perception of disaster preparedness is 2.68 ± 0.32. Respondents have attended 88.5% BHD training, 76.5% APAR, 60.8% fire simulation and 42.4% earthquake simulation. Disaster experiences and research locations influence the disaster preparedness of nurses in referral hospitals in Indonesia. There were no statistically significant differences in nurses’ preparedness for disasters on gender, education level, marital status, place of work, position. Conclusion. Nurses’ experience in dealing with disasters increases the perception of disaster preparedness among nurses. Therefore, regular training and simulations are required in the health services of disaster-prone areas in Indonesia.